Scholars, Spice Traders, and Sultans: Arguing over the Alms-Tax in the Mamluk Era - Blecher, Joel (Islamic law and society, 2020)
Abstract Amidst the politics of the Mamluk-era spice route, why did the standard-bearers of Islamic law routinely oppose the sultanate’s imposition of an alms-tax on merchandise (zakāt al-tijāra), despite the abundance of support for such a tax within the classical tradition of Islamic law? Rather than contending – as some modern scholars have – that prominent jurists developed loopholes that circumvented the original intent of the law to protect the wealthy and the ruling class, I argue that it was precisely the jurists’ careful defense of exemptions and exclusions that allowed them to define the essence of zakāt against forms of taxation they considered unlawful. By narrowing the scope of zakāt, jurists attempted to achieve a moral aim that went beyond the ritual purification of wealth: a limit on the sultanate’s otherwise arbitrary power to tax Muslims as it wished. In doing so, they alleviated some of the tax burden for spice merchants and camel herders alike.